UMKM Sebagai Pilar Penting Perekonomian Indonesia: Kajian Pada UMKM Roti Bakar Desa Pendawan - Noviriani, Eliza; Prayokta, Septiyola (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
This study was conducted with the aim of knowing and analyzing the management functions of Bread Bake UMKM in Pendawan Village, namely discussing planning (planning) carried out by UMKM for their business, organizing (organizing) in the division of tasks for their operational activities, actuating (driving) that keeps the business afloat. To be able to compete and control (supervision) the preparation of financial reports in accordance with SAK EMKM using the Si Apik application. The results of the study show (1) planning is still a plan for the long term, business owners still do not have a plan in the short and medium term, (2) organizing in the division of tasks has been implemented, even though in a while if there is work which cannot be done by one of the workers can be replaced, (3) the actuating as the business owner has tried to make new innovations so that the business being run can survive and compete, (4) (controlling) in this case the preparation of financial reports is still not done applied by business owners to their businesses so that researchers also help make the preparation of financial reports using the Si Apik application in accordance with the SAK EMKM.